Beta decay of 66Mn to the N = 40 nucleus 66Fe. (2nd November 2017) - Olaizola, B; Fraile, L M; Mach, H; Poves, A; Aprahamian, A; Briz, J A; Cal-González, J; Ghiţa, D; Köster, U; Kurcewicz, W; Lesher, S R; Pauwels, D; et al.
Abstract: The low energy structure of 66 Fe was studied by means of γ - and fast-timing spectroscopy at the ISOLDE/CERN facility. The level scheme of 66 Fe populated following the β − decay of 66 Mn was established. It confirms and further expands the level scheme from recent publications. The β -delayed neutron emission branch was measured and γ rays in 65 Fe were observed following the β –n decay for the first time. The half lives of the 2 1 + state and four other states of 66 Fe were measured using the advanced time-delayed β γ γ ( t ) method. These results are compared with large-scale shell-model calculations based on the Lenzi–Nowacki–Poves–Sieja interaction. The β -decay of 66 Mn to 66 Fe has been calculated as well, and log( ft ) values derived. Spin and parity assignments are proposed based on the experimental information and the new calculations.